Revision of the ant genus melophorus (Hymenoptera, formicidae) - Heterick, Brian; Castalanelli, M.; Shattuck, S. (Pensoft Publishers, 2017)
© Brian E. Heterick et al. The fauna of the purely Australian formicine ant genus Melophorus (Hymenoptera: Formicidae) is revised. This project involved integrated morphological and molecular taxonomy using one mitochondrial gene (COI) and four nuclear genes (AA, H3, LR and Wg). Seven major clades were identified and are here designated as the M. aeneovirens, M. anderseni, M. biroi, M. fulvihirtus, M. ludius, M. majeri and M. potteri species-groups. Within these clades, smaller complexes of similar species were also identified and designated species-complexes. The M. ludius species-group was identified purely on molecular grounds, as the morphology of its members is indistinguishable from typical members of the M. biroi species-complex within the M. biroi species-group. Most species-complexes sampled were also found to be monophyletic. Sequencing generally supported monophyly in taxa sampled but some species of the M. fieldi complex and M. biroi were not monophyletic and the implications arising from this are discussed in this monograph. Based on morphology, ninety-three species are recognized, 73 described as new. A further new species (here called 'Species K' [TERC Collection]) is noted in the taxonomic list, but is not described in this work. One species is removed from Melophorus: M. scipio Forel is here placed provisionally in Prolasius. Six species and five subspecies pass into synonymy. Of the full species, M. constans Santschi, M. iridescens (Emery) and M. insularis Wheeler are synonymized under M. aeneovirens (Lowne), M. pillipes Santschi is synonymized under M. turneri Forel, M. marius Forel is synonymized under M. biroi Forel, and M. omniparens Forel is synonymized under M. wheeleri Forel. Of the subspecies, M. iridescens fraudatrix and M. iridescens froggatti Forel are synonymized under M. aeneovirens (Lowne), M. turneri aesopus Forel and M. turneri candidus Santschi are synonymized under M. turneri Forel and M. fieldi propinqua Viehmeyer is synonymized under M. biroi. Camponotus cowlei Froggatt is reinstated as a junior synonym of Melophorus bagoti Lubbock. In addition, the subspecies M. fieldi major Forel, M. ludius sulla Forel and M. turneri perthensis Forel are raised to species. A key to workers of the genus is supplied. A lectotype is designated for M. curtus Forel, M. sulla, and M. turneri.